Study of Array Waveguide of Tunnel Microwave Oven - Nie, Shaowu; Yang, Suxian; Hu, Yuelai; Huang, Hanying; Zhao, Siming (Current Microwave Chemistry, 2015)
In this paper, electromagnetic simulation software was used to model and simulate tunnel microwave ovens, and the waveguide array layout was studied. The simulation results had been verified by the temperature test. The simulation and experimental results showed that when the waveguide was arranged on the upper surface of the cavity, and the long side of the waveguide was interactively perpendicular, the microwave oven had characteristics of high transmission efficiency, good uniformity and high strength of electric field. Besides, the best single row layout was suitable for the microwave oven with multiple ranks waveguides.
Keywords: microwave oven